5-Fluorouracil-β-Cyclodextrin conjugates:Linker strategies to enhance the anticancer efficacy and reduce the side effects - Liangliang Hu; Ting Meng; Davies Marabada; Zhichao Jin; Qing Huang; Shijie Wei; Zhizhong Wang (Carbohydrate Polymer Technologies and Applications)
5-Fluorouracil (5-FU) serves as a first-line therapeutic agent for colorectal cancer, however, its utility is limited by a short half-life and significant cytotoxicity. This study focused on the construction of 5-Fluorouracil-β-Cyclodextrin polymers (5-FUSA-β-CD and 5-FUBA-β-CD) by covalent conjugation using linker strategies to address limitations. The cytotoxicity assays on human colon cancer cell lines HT-29 and normal colon epithelial cells NCM-460 demonstrated that the IC50 value of the 5-FUBA-β-CD conjugate for the HT-29 cells was 38.72 ± 0.13 μM, indicating superior antitumor activity compared to both 5-FUBA-β-CD and 5-FU. Additionally, the conjugate exhibited reduced cytotoxicity towards normal colon epithelial cells. Pharmacokinetic analyses revealed that 5-FUSA-β-CD and 5-FUBA-β-CD were eliminated slowly and their half-lives were longer than that of free 5-FU. Distinct linkers were meticulously designed and synthesized to generate 5-Fluorouracil-β-Cyclodextrin conjugates that exhibit differential anti-colon cancer activity and half-lives. These findings not only demonstrated that 5-Fluorouracil-β-Cyclodextrin conjugates exhibits superior antitumor activity and reduced toxicity but also suggest that the linker plays a crucial role in determining both the efficacy of drug conjugates as an anticancer agent and its associated adverse effects. Future designs of linker can be optimized for greater efficiency.